CALCULATION OF STATISTICAL PARAMETERS OF THE FLOW OF REQUIREMENTS ARISING IN PLOWING AGGREGATES. (Multidisciplinary Journal of Science and Technology, 2025)
The article covers the issue of analyzing the flow of demand arising in plowing units used in agriculture. During operation, tractors and working machines cause various malfunctions and maintenance requirements. These requirements have the character of a random process, and methods of probability theory and mathematical statistics are used for their analysis. The study examined 169 patients in the Namangan region during 2021-2023. The set of malfunctions noted in the plowing units of the Arion-630s during the autumn plowing season and the requirements for their elimination were studied. As a result, the main statistical parameters of the demand flow - mathematical expectation, variance, coefficient of variation - were determined, and an empirical histogram of the distribution was compiled. Based on the obtained data, the characteristics of the demand flow, subject to the exponential law, are substantiated, and the limits of the confidence interval are calculated. The research results are of practical importance in the effective planning of the maintenance system, determining the optimal location of service centers and repair shops.